STRATEGI KOMUNIKASI HUMAS KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KELAS III DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI KOTA PEKANBARU - Siti Fitria Santi; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Office of Kesyahbandaran and Port Authority of Pekanbaru III class as a service provider in the field of port services is still faced with problems in the field of public services. In addition, a lot of service users always ignore the schedule of service procedures that have been given, so that the service can not be given optimally. The purpose of this research is to know how communicator strategy, messaging strategy, and communication media strategy used by Public Relations The Office of Kesyahbandaran and Port Authority of Pekanbaru Class III in improving the quality of public service in Pekanbaru city.This study used qualitative research methods with the presentation of descriptive analysis. Subjects in this study consisted of seven people selected by using purposive technique which is determined based on criteria of informant who understand public relation and involved in service activity and service user at Kesyahbandaran Office and Port Authority of Class III Pekanbaru. Data collection techniques include interviews, observation and documentation. To achieve the validity of data in this study, the writer use extension of participation and triangulation.The results of research in this study indicate that the strategy communicators are determined from the attractiveness of resource and communicator credibility. The message strategy used is to use appropriate language and word selection, directly to the main point of the problem, and use a message call in the form of a slogan or call. While the communication media used is consists of direct media or face-to-face,internet media in the form of official website and payment system through E-Biling System and mass nonmedia in the form of use of information board and ID Card for service user and visitor (guest).Keywords: Communication Strategy,Quality,Public Service